The poetry of US : with favorites from Maya Angelou, Walt Whitman, Gwendolyn Brooks and more - Lewis, J. Patrick (National Geographic, 2018)
Compiles over 200 new and familiar poems celebrating the people and places of the United States curated by former U.S. Children's Poet Laureate J. Patrick Lewis. Organized by geographical region, the poems feature the cultures, traditions, and histories of fifty states and are accompanied by large color photographs.